(untitled) (Revista LIDER, 2020)
Solid waste management arises for a balanced local / regional development, linking economic, social and environmental dimensions. The article proposes that inter municipal consortia are a viable alternative to rationalize the use of resources, and increase the capacity of cooperation in regional public policies. It presents the experience of the Intermunicipal Consortium do Vale do Itajaí Middle (SC).